2013
DOI: 10.1590/s0036-46652013000300005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the ELISA-F29 test as an early marker of therapeutic efficacy in adults with chronic Chagas disease

Abstract: SUMMARYThis work compared the time at which negative seroconversion was detected by conventional serology (CS) and by the ELISA-F29 test on a cohort of chronic chagasic patients treated with nifurtimox or benznidazole. A retrospective study was performed using preserved serum from 66 asymptomatic chagasic adults under clinical supervision, and bi-annual serological examinations over a mean follow-up of 23 years. Twenty nine patients received trypanocide treatment and 37 remained untreated. The ELISA-F29 test u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
29
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 21 publications
1
29
0
5
Order By: Relevance
“…En la mayoría de los casos la detección de la enfermedad tiene lugar en las fases crónicas, cuando las secuelas ya mencionadas comienzan a ser más evidentes y el tratamiento antiparasitario parece no ser tan efectivo (14,22) .…”
Section: Manejo Actual De La Tripanosomiasis Americanaunclassified
See 2 more Smart Citations
“…En la mayoría de los casos la detección de la enfermedad tiene lugar en las fases crónicas, cuando las secuelas ya mencionadas comienzan a ser más evidentes y el tratamiento antiparasitario parece no ser tan efectivo (14,22) .…”
Section: Manejo Actual De La Tripanosomiasis Americanaunclassified
“…Los tratamientos antitripanocidas han demostrado en algunos estudios una efectividad cercana al 100%; como el caso de un seguimiento realizado a un grupo de 66 pacientes, de los cuales 29 fueron sometidos a tratamiento con benznidazol y nifurtimox, en donde se obtuvo un xenodiagnóstico negativo después de un período de 15 años en 93,1% de los pacientes tratados (22) ; sin embargo, los resultados de otros estudios no son tan alentadores, pues demuestran bajas tasas de curación, tanto en animales como en humanos (9) .…”
Section: Manejo Actual De La Tripanosomiasis Americanaunclassified
See 1 more Smart Citation
“…During the development of reliable tools to evaluate the therapeutic efficacy of drugs for Chagas disease, several markers have been proposed and, in some cases, have been demonstrated to be effective for assessing the responses to specific treatments (19)(20)(21)(22)(23). Previous laboratory studies showed that the KMP11, PFR2, HSP70, and 3973 T. cruzi antigens are recognized with high specificity and sensitivity in the sera from patients in the chronic stage of the disease (21,24).…”
mentioning
confidence: 99%
“…En la fase aguda de la enfermedad de Chagas se establecen cifras serológicas de curación cercanas al 100 % (Fabbro et al, 2013), pero en la fase crónica se ha estimado que tan solo 5.9 % de los pacientes que reciben tratamiento alcanzan a curarse (Matta, Gutierrez, Nascimiento, DoValle, & Silva, 2012). Las reacciones adversas frecuentemente son causa de suspensión del tratamiento, pueden presentarse hasta en el 40 % de los pacientes tratados con benznidazol y el 61 % de los tratados con nifurtimox (Carrilero, Murcia, Martinez-Lage, & Segovia, 2011;Murcia, Carrilero, Viñas, & Segovia, 2012).…”
unclassified